Parents' and providers' attitudes toward school-located provision and school-entry requirements for HPV vaccines. Issue 6 (2nd June 2016) - Vercruysse, Jessica; Chigurupati, Nagasudha L.; Fung, Leslie; Apte, Gauri; Pierre-Joseph, Natalie; Perkins, Rebecca B.
ABSTRACT: Objective : To determine parents' and providers' attitudes toward school-located provision and school-entry requirements for HPV vaccination.Methods : Parents/guardians of 11–17 y old girls and pediatric healthcare providers at one inner-city public clinic and three private practices completed semi-structured interviews in 2012-2013. Participants were asked open-ended questions regarding their attitudes toward school-located provision and school-entry requirements for HPV vaccination. Parents' answers were analyzed with relationship to whether their daughters had not initiated, initiated but not completed, or completed the HPV vaccine series. Qualitative analysis was used to identify themes related to shared views.Results : 129 parents/guardians and 34 providers participated. 61% of parents supported providing HPV vaccinations in schools, citing reasons of convenience, improved access, and positive peer pressure. Those who opposed school-located provision raised concerns related to privacy and the capacity of school nurses to manage vaccine-related reactions. Parents whose daughters had not completed the series were more likely to intend to vaccinate their daughters in schools (70%) and support requirements (64%) than parents who had not initiated vaccination (42% would vaccinate at school, 46% support requirements) or completed the series (42% would vaccinate at school, 32% support requirements; p < 0 .05 for all comparisons). 81% of providers supported offering vaccination in schools, wanting to take advantage of the captive audience, improve vaccine completion rates, and decrease the administrative burden on medical office staff, but were concerned about adequate information transfer between schools and medical offices. Only 32% of providers supported school-entry requirements, largely because they felt that a requirement might provoke a public backlash that could further hinder vaccination efforts.Conclusions : School-located provision of HPV vaccination was widely accepted by healthcare providers and parents whose children have not completed the series, indicating that this venue might be a valuable addition to improve completion rates. Support for school-entry requirements was limited among both parents and healthcare providers.